2015
DOI: 10.3892/ol.2015.3646
|View full text |Cite
|
Sign up to set email alerts
|

Emodin induces apoptosis of human breast cancer cells by modulating the expression of apoptosis-related genes

Abstract: Abstract. The aim of this study was to investigate the effects of emodin on the proliferation of human breast cancer cells . Cell viability following emodin treatment was assessed by 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay. The effects of emodin on apoptosis were determined by flow cytometry using Annexin V-fluorescein isothiocyanate and propidium iodide staining. Quantitative polymerase chain reaction and western blot analysis were used to determine changes in the expression o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
30
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(32 citation statements)
references
References 32 publications
2
30
0
Order By: Relevance
“…Breast cancer has been reported to be associated with the aberrant expression of oncogenes [13]. Despite the improvements in the diagnosis, treatment and prognosis prediction of breast cancer, it remains the most prevalent malignant tumor with the high incidence in women worldwide.…”
Section: Discussionmentioning
confidence: 99%
“…Breast cancer has been reported to be associated with the aberrant expression of oncogenes [13]. Despite the improvements in the diagnosis, treatment and prognosis prediction of breast cancer, it remains the most prevalent malignant tumor with the high incidence in women worldwide.…”
Section: Discussionmentioning
confidence: 99%
“…Emodin (1,3,8-Trihydroxy-6-methylanthraquinone) is an anthraquinone natural extract of the rhizome of Polygonum cuspidatum and has a variety of pharmacological activities, including anticancer, anti-inflammation, antibacterial, diuretic and laxative etc. Recent studies have shown that emodin has inhibitory effects on various cancers such as colorectal cancer, liver cancer, prostate cancer, pancreatic cancer, cervical cancer and breast cancer by inducing the cellular apoptosis (14)(15)(16)(17).…”
mentioning
confidence: 99%
“…Bax is an apoptosis activator and triggers the release of cytochrome c and Smac-diablo (20). Our results have indicated that emodin is able to, at the same time, increase bax (encoding the pro-apoptotic protein Bax) expression and down -regulate bcl-2 (encoding the 6 Int J Cancer Manag.…”
Section: Discussionmentioning
confidence: 68%